Leaf photosynthesis and associations with grain yield, biomass and nitrogen-use efficiency in landraces, synthetic-derived lines and cultivars in wheat - Gaju, Oorbessy; deSilva, Jayalath G.; Carvalho, P.; Hawkesford, Malcolm J.; Griffiths, Simon; Greenland, Andrew; Foulkes, M.J. (Elsevier, 2016)
Future genetic progress in wheat grain yield will depend on increasing above-ground biomass and this must be achieved without commensurate increases in N fertilizer inputs to minimise environmental impacts. Our objective was to quantify variation in grain yield, above-ground biomass and N-use efficiency (NUE) and associated traits in a panel of diverse hexaploid wheat germplasm comprising: (i) landraces from the AE Watkins collection, (ii) synthetic-derived hexaploid lines in a cv. Paragon spring wheat background and (iii) UK modern cultivars including cv. Paragon under low N and high N conditions. A field experiment was carried out in two seasons examining 15 genotypes (five landraces, five synthetic-derived (SD) hexaploid lines and five UK modern cultivars) under low N and high N conditions at Nottingham University farm, UK. Machine-harvested grain yield, above-ground biomass and NUE were measured. Physiological traits were assessed including flag-leaf light-saturated photosynthetic rate (Amax) and relative chlorophyll content (SPAD) under HN conditions; and flag-leaf senescence duration and rate and Normalized Difference Vegetative Index (NDVI) under LN and HN conditions. Under HN conditions, the modern cultivars overall produced higher grain yield than the SD lines (+9.7%) and the landraces (+60.4%); and the modern cultivars and SD lines also produced higher biomass than the landraces (30.3% and 28.4%, respectively). Under LN conditions, reduction in grain yield and biomass compared to HN conditions was least for the landraces (−1% and −8.6%, respectively), intermediate for the SD lines (−7.4 and −10.2%, respectively) and highest for the modern cultivars (−9.3 and −24.6%, respectively). As a result, the SD lines had higher biomass (+17%) than the modern cultivars under LN conditions. Under HN conditions the synthetic derivatives (23.8 μmol m−2 s−1) and modern cultivars (241.1 μmol m−2 s−1) had higher pre-anthesis Amax than the landraces (19.7 μmol m−2 s−1) (P < 0.001). Pre-anthesis Amax was strongly positively linearly associated with above-ground biomass (R2 = 0.63, P < 0.001) and grain yield (R2 = 0.75, P < 0.001) amongst the 15 genotypes. Flag-leaf Amax was also positively linearly associated with flag-leaf relative chlorophyll content at anthesis (R2 = 0.74; P < 0.001). Comparing the SD lines to the recurrent parent Paragon, under HN conditions one line (SD 22) had higher pre-anthesis flag-leaf Amax than Paragon (P < 0.05). Under LN conditions one line (SD 24, +27%) had higher yield than Paragon (P < 0.05) and two lines (SD 24 and SD 38, +32% and +31%, respectively) had more biomass than Paragon (P < 0.05). Our results indicated that introgressing traits from synthetic-derived wheat and landraces into UK modern wheat germplasm offers scope to raise above-ground biomass and grain yield in moderate-to-low N availability environments.